A Review of the Valuation of Environmental Costs and Benefits in World Bank Projects - Silva, Patricia (World Bank, Washington, DC, 2014)
The review examines the use of environmental valuation in 101 projects in the World Bank's environmental portfolio approved in fiscal years 2000, 2001, and 2002. It has three broad objectives. First, it examines the extent to which environmental costs and benefits have been incorporated in the economic analysis of projects. Second, it examines how well valuation was used. Third, it seeks to identify areas of weakness so as to feed into plans for capacity building. The results show that the use of environmental valuation has increased substantially in the last decade. Ten years ago, one project in 162 used environmental valuation. In recent years, as many as one third of the projects in the environmental portfolio did so. While this represents a substantial improvement, there remains considerable scope for growth.